2002
DOI: 10.1200/jco.20.4.1075
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Adoptive Immunotherapy With Cytolytic T Lymphocytes Immunized Against a Tyrosinase Epitope

Abstract: CTLs immunized against a single melanoma epitope were nontoxic but did not specifically localize to tumor sites. Nevertheless, two patients had disease regression. Additional therapeutic studies with specifically immunized CTL seem justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Donor lymphocytes are radiolabeled with individual isotopes (e.g., 111 In, 125 I, 99m Tc) allowing for their detection in target tissues after adoptive transfer (Wallace et al, 1993). Furthermore, radiolabeling (which is typically detected ex vivo in murine tissues) has been applied in vivo, utilizing whole body scintigraphy imaging in human clinical trials (Cole et al, 1994;Itoh et al, 1988;Mitchell et al, 2002;Pockaj et al, 1994). However, the strategy of utilizing radiolabeled lymphocytes to study trafficking of AT cells is mostly inferential, dependent upon many variables and lacks qualitative data regarding phenotype, function or actual location of labeled cells within the target tissues.…”
Section: Methods Of Detectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Donor lymphocytes are radiolabeled with individual isotopes (e.g., 111 In, 125 I, 99m Tc) allowing for their detection in target tissues after adoptive transfer (Wallace et al, 1993). Furthermore, radiolabeling (which is typically detected ex vivo in murine tissues) has been applied in vivo, utilizing whole body scintigraphy imaging in human clinical trials (Cole et al, 1994;Itoh et al, 1988;Mitchell et al, 2002;Pockaj et al, 1994). However, the strategy of utilizing radiolabeled lymphocytes to study trafficking of AT cells is mostly inferential, dependent upon many variables and lacks qualitative data regarding phenotype, function or actual location of labeled cells within the target tissues.…”
Section: Methods Of Detectionmentioning
confidence: 97%
“…Radiolabeling as a technique to investigate lymphocyte trafficking is a well-established, but older method (Rannie and Donald, 1977;Wallace et al, 1993;Wiltrout et al, 1983) that remains one of the few strategies used in human studies (Mitchell et al, 2002;Pockaj et al, 1994). Donor lymphocytes are radiolabeled with individual isotopes (e.g., 111 In, 125 I, 99m Tc) allowing for their detection in target tissues after adoptive transfer (Wallace et al, 1993).…”
Section: Methods Of Detectionmentioning
confidence: 98%
“…It seems that the adoptive transfer of uncloned T cells can result in tumor regression more consistently [50]. It may be important to administer nonmyeloablative chemotherapy to neutralize suppressive regulatory T cells before infusing the T cells.…”
Section: Adoptive Cell Transfermentioning
confidence: 98%
“…Ten patients with different stages of metastatic melanoma were enrolled in the study; none of the patients showed signs of toxicity after administering the T cells. When the distribution of the transferred T cells was monitored, homing to the tumor lesions, which had been reported with DC-stimulated T cells [34], could not be detected, and T cells found in biopsies of lesions were not clearly antigen specific [74].…”
Section: Mhc-class-ii-based Antigen-specific Aapcsmentioning
confidence: 98%
“…Drosophila-based aAPCs (expressing HLA-A2, CD80 and CD54) (Figure 2c), as discussed above, have also been used to generate clinical-grade antigen-specific T cells against the melanoma antigen tyrosinase [74]. After an initial round of T-cell induction with the aAPCs, these were replaced by autologous APCs for two additional rounds of stimulation.…”
Section: Mhc-class-ii-based Antigen-specific Aapcsmentioning
confidence: 99%